Konservasi In Vitro Jenis Tumbuhan Gambut Tumih (Combretocarpus rotundatus (Miq.) Danser) - Istomo Istomo; Edhi Sandra; Vianti Vianti; Mufti Abdillah (HUTAN TROPIKA, 2023)
Tumih (Combretocarpus rotundatus (Miq.) Danser) is one of the local species recommended for disturbed peatland rehabilitation activities. This species can be classified as a fast-growing and tolerant type to dry and open conditions. The aim of this study is to identify the success of explant preparation techniques and tumih explant sterilization seen from the survival rate, contamination level, and browning level. The research was conducted at the Environmental Biotechnology Laboratory, Environmental Research Center (PPLH), IPB. The plant material used was tumih shoots that were sterilized using detergent, HgCl2, Clorox, and rinsed with sterile water. The explants were initiated on MS media with the addition of BAP, namely 0 ml/l; 0.5 ml/l; 1 ml/l; and 1.5 ml/l, and TDZ, namely 0 ml/l; 0.05 ml/l; 0.1 ml/l; and 0.5 ml/l. This study used 16 treatments with 7 replications. The results showed that the average survival rate percentage of tumih explants reached 22.32%, fungal contamination was 57.14%, bacterial contamination was 1.79%, and the average browning percentage in the explants was 18.75%. The preliminary study that has been carried out is categorized as successful, with 25 explants still maintaining green leaves and stems